Cushing’s Syndrome and Hypothalamic–Pituitary–Adrenal Axis Hyperactivity in Chronic Central Serous Chorioretinopathy - van Haalen, Femke M.; van Dijk, Elon H. C.; Dekkers, Olaf M.; Bizino, Maurice B.; Dijkman, Greet; Biermasz, Nienke R.; Boon, Camiel J. F.; Pereira, Alberto M. (Frontiers in Endocrinology, 2018)
Objective: Central serous chorioretinopathy (CSC), a specific form of macular degeneration, has been reported as presenting manifestation of Cushing’s syndrome. Furthermore, CSC has been associated with both exogenous hypercortisolism and endogenous Cushing’s syndrome. It is important to know whether CSC patients should be screened for Cushing’s syndrome. Although hypothalamic-pituitary-adrenal (HPA) axis hyperactivity in CSC has been suggested, no detailed evaluation of the HPA axis has been performed in a large cohort of CSC patients. This study aimed to investigate whether Cushing’s syndrome prevalence is increased among chronic CSC (cCSC) patients and whether detailed endocrinological phenotyping indicates hyperactivity of the HPA axis. Design: Cross-sectional study. Patients: 86 cCSC patients and 24 controls. Measurements: Prevalence of Cushing’s syndrome, HPA axis activity. Results: None of the cCSC patients met the clinical or biochemical criteria of Cushing’s syndrome. However, compared to controls, HPA axis activity was increased in cCSC patients, reflected by higher 24 hour urinary free cortisol, and accompanying higher waist circumference and diastolic blood pressure, whereas circadian cortisol rhythm and feedback were not different. Chronic CSC patients did not report more stress or stress-related problems on questionnaires. Conclusions: No case of Cushing’s syndrome was revealed in a large cohort of cCSC patients. Therefore, we advise against screening for Cushing’s syndrome in CSC patients, unless additional clinical features are present. However, our results indicate that cCSC is associated with hyperactivity of the HPA axis, albeit not accompanied with perception of more psychosocial stress.